Taxonomic review of Thoracostomopsidae (Nematoda, Enoplida): state of the art, list of valid species and dichotomous keys - Souza, João V. De; Maria, Tatiana F. (Zootaxa, 2023)
Thoracostomopsidae is a family of free-living marine nematodes that has three subfamilies (Thoracostomopsinae, Trileptiinae and Enoplolaiminae). Most species descriptions within this family are very old and lack indication of important morphological details, so this article aims to fill this gap in the literature. This taxonomic review provides a list of all valid species, as well as species inquirenda, nomina nuda and synonyms, for each genus. Our review recognizes 16 valid genera, 193 valid species, 47 species inquirendae and three species as nomen nudum. Additionally, taxonomic dichotomous keys were constructed, modified or updated for each genus, as well to the subfamilies, using the most important diagnostic characters.